2015
DOI: 10.1038/pr.2015.240
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hematocrit on in vitro bilirubin photoalteration

Abstract: Background: Phototherapy using light in the spectral range of 410-500 nm, which overlaps the absorption of bilirubin, is the common treatment for neonatal hyperbilirubinemia. Hemoglobin (Hb) absorbs light strongly throughout this same range and thus can compete with bilirubin for this light and consequently reduce the efficacy of phototherapy. Here, we determined the effect of hematocrit (Hct) on in vitro bilirubin photoalteration using narrow-band blue (450 nm) lightemitting diodes (LEDs). Methods: Suspension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…In another in vitro study, by Lamola et al (4), using a semiempirical skin model, it was confirmed that hemoglobin in the skin competes with bilirubin for absorption of light during phototherapy. This was strongest at the wavelength 400-460 nm, also found in vitro by Linfield et al (5) in 2016. On the basis of these results, it was predicted that a high hematocrit would reduce the therapeutic efficacy of phototherapy in vivo.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In another in vitro study, by Lamola et al (4), using a semiempirical skin model, it was confirmed that hemoglobin in the skin competes with bilirubin for absorption of light during phototherapy. This was strongest at the wavelength 400-460 nm, also found in vitro by Linfield et al (5) in 2016. On the basis of these results, it was predicted that a high hematocrit would reduce the therapeutic efficacy of phototherapy in vivo.…”
Section: Discussionsupporting
confidence: 75%
“…Whether the biochemical processes during phototherapy occur predominantly intravascularly or extravascularly has long been debated, although recent evidence strongly supports the idea that the biochemical processes during phototherapy predominantly take place intravascularly. In these in vitro studies, it has also been found that hemoglobin is a major competitor with bilirubin for the absorption of light during light exposure (4,5). The authors predicted that a high hematocrit would reduce the therapeutic efficacy of phototherapy; however, this has never been confirmed in vivo (4,5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous animal experiments showed that skin bilirubin of jaundiced rats under blue or green light irradiation was converted to metastable geometric isomers, which were then transported in the blood and excreted in the bile3334. The same reaction probably occurred in light-exposed jaundiced babies, particularly during phototherapy.…”
Section: Resultsmentioning
confidence: 96%
“…As the transformation of Z,Z-bilirubin predominantly takes place intravascularly, hemoglobin will compete with bilirubin for the absorption of light [38,39]. An increase in hemoglobin concentration decreased the percentage of Z,E-bilirubin in plasma in the first hour of PT but this effect disappeared later [19].…”
Section: Fect Of Phototherapymentioning
confidence: 99%